No exit [compact disc, unabridged] - Adams, Taylor (Brilliance Audio, 2018)
Darby Thorne is a college student stranded by a blizzard at a highway rest stop in the middle of nowhere. She's on the way home to see her sick mother. She'll have to spend the night in the rest stop with four complete strangers. Then she stumbles across a little girl locked inside one of their parked cars.